Tuesday
March 28, 2017

Post a New Question

Posted by on .

How do I solve e^(2x)+10e^(x)-75=0 and 3^(x+2)=7^(x-5)?

  • Pre Calc - ,

    For e^(2x)+10e^(x)-75=0
    Let
    y=e^x
    then
    y² = e^(2x)
    Substitute in above equation,
    y²+10y-75=0
    Factor and solve for y.
    Note that the domain of y (=e^x) is (0,∞), so any negative root for the quadratic equation must be rejected.

    For 3^(x+2)=7^(x-5)
    take logarithm on both sides, and apply the exponent rule to get
    (x+2)*ln 3 = (x-5)*ln 7
    Solve for x. I get x=14 approx.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question